1988
DOI: 10.1098/rspa.1988.0038
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations of simple exothermic reactions in a closed system. II. Exact Arrhenius kinetics

Abstract: The simplest model of thermokinetic oscillations in a closed, chemical system requires only two first-order reaction steps (0) P → A rate = k 0 p , (1) A → B rate = k 1 ( T ) a . Step (0) is assumed to be thermoneutral and its rate constant to not depend on the temperature (i. e. to have zero activation energy). Step (1) is an exothermic process, and the rate constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…In a later paper, Kay and Scott [11] analysed the exact equations with the full exponential non-linearity, and showed that there are parameter regions in which use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S0334270000009103 two oscillatory solutions can exist simultaneously; one of these is stable and the other unstable.…”
Section: Rt Amentioning
confidence: 99%
“…In a later paper, Kay and Scott [11] analysed the exact equations with the full exponential non-linearity, and showed that there are parameter regions in which use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S0334270000009103 two oscillatory solutions can exist simultaneously; one of these is stable and the other unstable.…”
Section: Rt Amentioning
confidence: 99%
“…Previous theoretical studies of such a system have focussed largely on two limiting cases of behaviour, namely the well-mixed, spatially uniform case obtained with forced convection, (see e.g. Kay and Scott 1988;Gray and Roberts 1988;Forbes 1990;Gray and Scott 1990a) when the effects of diffusion can be neglected, and the case with purely diffusive transport of heat and mass (Gray and Scott 1990b).…”
Section: Introductionmentioning
confidence: 99%
“…An approximate solution, based on integrated forms of the boundary-layer equations can be constructed. This leads to a system of equations similar to the Sal'nikov scheme, discussed in detail by Kay and Scott [21,22]. The corresponding steady states of this approximate solution have all the features of the present problem (saddle-node bifurcations and hysteresis points) as well as supercritical Hopf bifurcations, suggesting that these could also be a feature of the present initial-value problem (7).…”
Section: Time Dependent Problemmentioning
confidence: 79%
“…Finally we note that (22) implies that the critical points become large, of 0((_ 4 ), as --> . In particular…”
Section: Non Fuel Consumption Case (A = 0)mentioning
confidence: 99%